Accompanying the Graduation of Military History S1 Cadet Cadets at the Indonesian Defence University - Subiantoro, Yudi; Manurung, Hendra; Pertiwi, Yuliana Anggun (JIMAD : Jurnal Ilmiah Multidisiplin, 2024)
On May 22, 2024, 25 students together with 326 cadet students from the Military History study program at the Indonesian Defence University were declared to have graduated as cadets and were entitled to take basic military education. This national military education Chandradimuka is for the Defence University Cadet students held at Indonesia Military Academy Magelang, Central Java. This activity will last for 3 full months of military education. Lieutenant General Armed Forces (TNI) Jonni Mahroza, Ph.D., opened the Basic Military Education (Diksarmil) Chandradimuka Undergraduate Student Cadet (S-1) Cohort 5 of the Indonesian Defence University for the 2024 Academic Year which was attended by 351 people who will carry out education for 3 months at Sapta Marga Field, city of Magelang. The Defence University of the Republic of Indonesia is a state university that provides vocational, undergraduate, and postgraduate education in the fields of defence and national defence, to carry out development and development oriented towards the Tri Dharma of higher education, to achieve national education standards and world-class university standards along with preserving national values. The results are that the implementation of this basic military training is the initial stage for Indonesian Defence University student cadets in the process of becoming defence human resources of excellence and integrity. This activity aims to shape the character of Indonesian Defence University student cadets into individuals who are disciplined and have integrity and responsibility. In the current era of globalization, Indonesia will certainly experience various challenges that will be increasingly complex and dynamic, so a young generation is needed who has high mental and physical resilience of national value and national defence.